2019
DOI: 10.3791/59219
|View full text |Cite
|
Sign up to set email alerts
|

Using the Open-Source MALDI TOF-MS IDBac Pipeline for Analysis of Microbial Protein and Specialized Metabolite Data

Abstract: In order to visualize the relationship between bacterial phylogeny and specialized metabolite production of bacterial colonies growing on nutrient agar, we developed IDBac-a low-cost and high-throughput matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) bioinformatics pipeline. IDBac software is designed for non-experts, is freely available, and capable of analyzing a few to thousands of bacterial colonies. Here, we present procedures for the preparation of bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 11 publications
(9 reference statements)
1
29
0
Order By: Relevance
“…Library isolates were prepared for bioinformatics analysis using IDBac, a matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry pipeline that allows for rapid analysis of microbial proteins and specialized metabolites. 17,20 The standard IDBac workflow uses a 70% aqueous formic acid solution to lyse cells but we found that this procedure was not efficient at lysing the more mucoid bacterial colonies isolated. 20 A trifluoroacetic acid (TFA) extraction prior to plating samples for analysis was the most effective method to consistently collect viable MS fingerprint profiles for IDBac analysis.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Library isolates were prepared for bioinformatics analysis using IDBac, a matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry pipeline that allows for rapid analysis of microbial proteins and specialized metabolites. 17,20 The standard IDBac workflow uses a 70% aqueous formic acid solution to lyse cells but we found that this procedure was not efficient at lysing the more mucoid bacterial colonies isolated. 20 A trifluoroacetic acid (TFA) extraction prior to plating samples for analysis was the most effective method to consistently collect viable MS fingerprint profiles for IDBac analysis.…”
Section: Resultsmentioning
confidence: 94%
“…17,20 The standard IDBac workflow uses a 70% aqueous formic acid solution to lyse cells but we found that this procedure was not efficient at lysing the more mucoid bacterial colonies isolated. 20 A trifluoroacetic acid (TFA) extraction prior to plating samples for analysis was the most effective method to consistently collect viable MS fingerprint profiles for IDBac analysis. 21 Measuring proteins in the 3,000 to 15,000 Da range, IDBac organized the microbial isolates into a pseudo-phylogeny dendrogram based on MS fingerprint protein similarity.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…IDBac analysis reveals that the addition of insoluble fiber supports an equally diverse cultivation of gut microbes as traditionally nutrient-rich media Library isolates were prepared for bioinformatics analysis using IDBac, a matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry pipeline that allows for rapid analysis of microbial proteins and secondary metabolites. 15,17 The standard IDBac workflow uses a 70% aqueous formic acid solution to lyse cells but we found that this procedure was not efficient at lysing the more mucoid bacterial colonies isolated. 17 A trifluoroacetic acid (TFA) extraction prior to plating samples for analysis was the most effective method to consistently collect viable MS fingerprint profiles for IDBac analysis.…”
Section: Addition Of Insoluble Fiber To Low Nutrient Agar Plates Incrmentioning
confidence: 98%